Active RNA polymerases are localized within discrete transcription "factories' in human nuclei. - Iborra, F; Pombo, A; Jackson, D; Cook, P (1996)
Nascent transcripts in permeabilized HeLa cells were elongated by approximately 30-2,000 nucleotides in Br-UTP or biotin-14-CTP, before incorporation sites were immunolabelled either pre- or post-embedding, and visualized by light or electron microscopy. Analogues were concentrated in approximately 2,100 (range 2,000-2,700) discrete sites attached to a nucleoskeleton and surrounded by chromatin. A typical site contained a cluster (diameter 71 nm) of at least 4, and probably about 20, engaged polymerases, plus associated transcripts that partially overlapped a zone of RNA polymerase II, ribonucleoproteins, and proteins rich in thiols and acidic groups. As each site probably contains many transcription units, these results suggest that active polymerases are confined to these sites, which we call transcription 'factories'. Results are consistent with transcription occurring as templates slide past attached polymerases, as nascent RNA is extruded into the factories.